1990
DOI: 10.1007/bf00154991
|View full text |Cite
|
Sign up to set email alerts
|

Buffer capacity and lead retention in some clay materials

Abstract: The link between buffer capacity and the ability of clays to retain Pb in interactions between Pb contaminant leachate and the clays, has been studied, using a natural clay from Quebec and laboratoryprepared clays (kaolinite, illite, and smectite). The retention of Pb in the clay suspensions as they received increasing amounts of acid was investigated, and the results examined in terms of the buffer capacity of the clays. As the clays receive increasing amounts of acid (e.g. akin to addition of acid leachate),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 15 publications
(2 reference statements)
4
56
0
2
Order By: Relevance
“…Reactive sorbent minerals such as Fe / Mn / Al-(hydr)oxides are present in large amounts in LDDS and these metals have high affinity for Fe / Mn / Al -(hydr)oxides (Kinniburgh et al, 1976). In addition, the neutral to slightly alkaline pH of the sediments favored strong adsorption of these metals on oxides and hydroxides of iron and manganese as well as on the clay mineral surfaces (Brümmer, 1986;Yong et al, 1990). Sorption of these minerals is qualitatively consistent with observed leaching patterns, the affinity of metals for these minerals increasing with increasing pH.…”
Section: Actual Leachabilitymentioning
confidence: 99%
“…Reactive sorbent minerals such as Fe / Mn / Al-(hydr)oxides are present in large amounts in LDDS and these metals have high affinity for Fe / Mn / Al -(hydr)oxides (Kinniburgh et al, 1976). In addition, the neutral to slightly alkaline pH of the sediments favored strong adsorption of these metals on oxides and hydroxides of iron and manganese as well as on the clay mineral surfaces (Brümmer, 1986;Yong et al, 1990). Sorption of these minerals is qualitatively consistent with observed leaching patterns, the affinity of metals for these minerals increasing with increasing pH.…”
Section: Actual Leachabilitymentioning
confidence: 99%
“…The latter elements are usually found to be less mobile. This is because at pH 4, Pb and Cu are still strongly retained by iron-oxides (Kinniburgh et al, 1976), organic matter (Brümmer, 1986;Livens, 1991) or clay minerals (Yong et al, 1990;Cavallaro & McBride, 1984), this in contrast to Cd or Zn. On the contaminated soil MG, sequential extraction was performed according to the BCR sequential extraction scheme (Queveauviller et al, 1994).…”
Section: Potential Leachabilitymentioning
confidence: 99%
“…In sorption experiments with various clay minerals, Yong et al, ( 1990) found that substantial amounts of Pb were retained even at pH2.…”
Section: Discussionmentioning
confidence: 99%